2016
DOI: 10.3928/01484834-20160414-02
|View full text |Cite
|
Sign up to set email alerts
|

Work Factors of Importance to Adjunct Nursing Faculty

Abstract: Using these data, colleges of nursing may be able to identify adjunct work factors in that can be improved to increase adjunct faculty recruitment, satisfaction, and retention. [J Nurs Educ. 2016;55(5):245-251.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
4
6
0
Order By: Relevance
“…New adjunct faculty who want to improve their knowledge may have poor access to university resources, as these opportunities often are offered when the adjunct faculty are not available. This supports previous findings that nursing adjunct faculty often have full-time jobs and do not have the time or inclination to devote to teaching issues (Elder et al, 2016). Similar to the present study, Elder et al (2016) also found that adjunct faculty are not being oriented, evaluated, and given the resources that regular faculty receive.…”
Section: Objective 3: Ot Adjunct Faculty Perceptions Of Their Use Andsupporting
confidence: 91%
See 4 more Smart Citations
“…New adjunct faculty who want to improve their knowledge may have poor access to university resources, as these opportunities often are offered when the adjunct faculty are not available. This supports previous findings that nursing adjunct faculty often have full-time jobs and do not have the time or inclination to devote to teaching issues (Elder et al, 2016). Similar to the present study, Elder et al (2016) also found that adjunct faculty are not being oriented, evaluated, and given the resources that regular faculty receive.…”
Section: Objective 3: Ot Adjunct Faculty Perceptions Of Their Use Andsupporting
confidence: 91%
“…Having a mentor in place was not only perceived as an indicator of readiness to teach but also as a needed support to transition successfully to academia from clinical practice. The need for mentoring described by the OT participants is consistent with the findings of previous allied health profession studies (Eaton et al, 2015;Falzarano & Zipp, 2012;Franz & Smith, 2013;Schoening, 2013). In fact, one of the participants in this study echoed one of Franz and Smith's (2013) participants when speaking of mentoring and having someone available to act as a guide and answer questions.…”
Section: Objective 3: Ot Adjunct Faculty Perceptions Of Their Use Andsupporting
confidence: 86%
See 3 more Smart Citations